2011
DOI: 10.2478/v10156-010-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of geoid models over Alaska computed with different Stokes' kernel modifications

Abstract: Abstract:Various Stokes kernel modification methods have been developed over the years. The goal of this paper is to test the most commonly used Stokes kernel modifications numerically by using Alaska as a test area and EGM08 as a reference model. The tests show that some methods are more sensitive than others to the integration cap sizes. For instance, using the methods of Vaníček and Kleusberg or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The use of the unmodified [spherical] Stokes kernel (zero on the X-axis in Figure 9) gives worse results because it is not as powerful a filter as the modified kernels (cf. Vanicek and Featherstone 1998), and is consistent with results found in Australia (e.g., Featherstone et al 1998Featherstone et al , 2011Featherstone et al , 2017 and elsewhere (e.g., Li and Wang 2011). The preferred quasigeoid solution was computed with an integration cap of 2.5 degrees and a Wong and Gore (1969) modification degree of 160.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The use of the unmodified [spherical] Stokes kernel (zero on the X-axis in Figure 9) gives worse results because it is not as powerful a filter as the modified kernels (cf. Vanicek and Featherstone 1998), and is consistent with results found in Australia (e.g., Featherstone et al 1998Featherstone et al , 2011Featherstone et al , 2017 and elsewhere (e.g., Li and Wang 2011). The preferred quasigeoid solution was computed with an integration cap of 2.5 degrees and a Wong and Gore (1969) modification degree of 160.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, quasigeoid solutions determined using modification degrees greater than 120 produced unreliable solutions, where the standard deviation of the quasigeoid/GPS-levelling differences varied drastically and were highly sensitive to the choice of integration cap. This is due to the instability of this kernel for high modification degrees, as noted in Featherstone (2003); also see Li and Wang (2011). We obtained more consistent results for the higher modification degrees using the Wong and Gore (1969) modified kernel.…”
Section: Discussionsupporting
confidence: 60%
“…If the condition numbers are used, it can be shown that the matrix of normal equations for Molodensky coefficients is always well conditioned. More recently, Li and Wang (2011) determined that Alaskan geoid models computed from the spheroidal Molodensky modification coefficients were variable depending on the choices of ψ o and L. They, however, used the real rather than a synthetic field for their tests and such results should have been expected. Table 2 Condition numbers for the combinations tested in this paper Another, perhaps more plausible, explanation is the size of the integration domain ψ o in relation to the choice of L. Specifically, if a small ψ o is used, the NZ integration cannot sense lower frequencies that may have not been removed by the degree-L RF.…”
Section: The ψ O and L Invariance Enigmamentioning
confidence: 99%
“…where ψ 0 is the spherical cap distance of the truncation radius, L is the degree of Molodensky modification (Molodensky et al 1962), which should be set smaller than n max , p is the degree of Wong and Gore modification (Wong and Gore, 1969), which is set equal to L in practice, t k is the kth Vanicek and Kleusberg modification coefficient (Vanićek and Kleusberg 1987), P k is the kth degree Legendre function. The application of Wong and Gore modification replaces the low-degree contributions from terrestrial gravity data with those from the GGM, whereas those of Molodensky modification and Vanićek and Kleusberg modification minimize the L 2 norm of the error kernel for the selected ψ 0 and L (Li and Wang, 2011). Therefore, unlike the Meissl kernel (namely L = 0), the FEO kernel not only reduces the truncation error but also optimally combines terrestrial gravity data with the GGM when the appropriate modification parameters (ψ 0 and L) are selected.…”
Section: Residual Cogeoid Heightmentioning
confidence: 99%